Left ventricular outflow tract obstruction after transcatheter mitral valve replacement: a case report with a multifaceted approach - Caneiro-Queija, Berenice; Guerreiro, Claudio E.; Echarte-Morales, Julio; Estévez-Loureiro, Rodrigo; Barreiro-Pérez, Manuel; González-Ferreiro, Rocío; Estévez-Cid, Francisco; Legarra, Juan José; Baz, Jose Antonio; Íñiguez-Romo, Andrés (Frontiers in Cardiovascular Medicine, 2024)
A 83-year-old woman was admitted to our Institution due to heart failure. Transthoracic echocardiography revealed severe MAC conditioning double mitral lesion. After Heart Team discussion a transcatheter mitral valve replacement (TMVR) with Tendyne (Abbott Structural, Santa Clara, CA, USA) was performed. Despite having a predicted neo-left ventricular outflow tract (LVOT) above the cut-off value, the patient developed clinically significant LVOT obstruction refractory to medical therapy After taking into consideration patient's anatomy we decided to perform alcohol septal ablation (ASA). In this case report we discuss this event and the available strategies to prevent and manage this condition.